Microstructural and mechanical properties evaluation of dissimilar aluminum alloy and bronze joints using friction stir welding. (2021) - Makeshkumar, M.; Surender, S.R.; Arunprakash, S.; Madesh, R.; Sasi Kumar, M.; Sudharsan, K.
Abstract: The current research work discusses on the mechanical and metallurgical studies of process of joining aluminium alloy and bronze by using friction stir welding method. The dimensions of base and substrate materials is considered as 100 mm × 50 mm × 4 mm. H13 Tool Steel with conical shape is utilized as a tool and the diameter of shoulder is chosen as 40 mm. The various process parameters such as speed of welding, rotational speed of tool, tilt angle of tool and axial force are considered as the most influencing parameters in this work. The welding speed affects the mechanical properties of friction stir welding weldments. Hence, the experiments are carried out to evaluate hardness and tensile strength of the friction stir weld joint. The output of tensile test suggested that speed of the welding 20 mm/min exhibits a high tensile strength of 94.5 MPa. In addition, maximum hardness value of 75 BHN is attained at the welding 20 mm/min welding speed. From the experimental study, the optimal process parameters are found as 10 kN axial force, 1125 rpm rotational speed, 20 mm/min welding speed and 2° tilt angle of the tool. Further microstructure studies of FSW welded joint resulted that there is existence of reinforcement and even spreading of the particles all over the weld region. Selection and/or Peer-review under responsibility of International Conference on Sustainable materials, Manufacturing and Renewable Technologies (i-SMaRT 2021)